THE STATE OF ANTIOXIDANT SYSTEM OF THE WOMEN UNDERGOING THE PROCEDURE OF IN VITRO FERTILIZATION - M. Yu. Prorubschikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The antioxidant system activity was studied in 74 patients undergoing infertility treatment by the vitro fertilization, depending on the effectiveness of the procedure.